Nitrous oxide emissions from agricultural peat soils in southern and northern Finland - Hannukkala, Antti; Esala, Martti; Syväsalo, Eija; Regina, Kristiina (Agricultural Research Centre Ghent (CLO-GENT), 2001)
v ok mkf